Análise de eficiência de produtores de leite em assentamento rural - Barbieri, Rayner Sversut [UNESP]; De Oliveira, Laura Britto Garcia [UNESP]; Sabbag, Omar Jorge [UNESP] (My University, 2016)
In Brazil, the agro-industrial chain of milk has great economic and social importance. Rural settlements whose main productive activity in dairy farming due to a number of factors, but the main reason to adopt this activity is the guarantee of minimum monetary entries every month. Aimed to analyze the efficiency of milk production through data envelopment analysis (DEA). The results showed that only 37.5% were efficient, implying that the producer must consciously use their resources and inputs according to its production planning.
Dairy farmers of efficiency analysis in rural settlement
Keywords: Dairy cattle; DEA analysis; Rural development